The morning ritual in the Talmud. The reconstitution of one's body and personal identity through the blessings - Marḳs, Dalyah (Hebrew Union College annual / Jewish Institute of Religion, 2006)
The simple, routine acts of going to sleep each night and awakening each morning were perceived by the Rabbis as experiences not without facets of crisis. This article examines the talmudic liturgical response that came to help people cope with this daily (even if minor) crisis. The liturgical body of the Morning Blessings (birkhot hashaḥar) is found in the Babylonian Talmud, Berakhot 60b. This sequence of blessings will be discussed in light of the theory of rites of passage that was first articulated by Arnold Van Gennep and later developed by Victor Turner. This theory deals with rituals that are performed at the essential crossroads of life; such rituals not only mark a transition in status, but also effect it. The article examines the narrative created by the sequence of the Morning Blessings, and aims to demonstrate that together they comprise a qualitative transformational experience helping the one who recites them to make a transition from the nocturnal state of existence to the daytime. This is a relatively minor transition, but its goal is apparently to move from a status of symbolic death to a state of life and activity, of control, enterprise, and appropriate Jewish lifestyle.